Outcomes of patients with loco-regionally recurrent or new primary squamous cell carcinomas of the head and neck treated with curative intent reirradiation at Mayo Clinic. Issue 1 (December 2016) - Curtis, Kelly; Ross, Helen; Garrett, Ashley; Jizba, Theresa; Patel, Ajay; Patel, Samir; Wong, William; Halyard, Michele; Ko, Stephen; Kosiorek, Heidi; Foote, Robert
Abstract Background We reviewed outcomes of patients with loco-regionally recurrent (LRR) or new primary (NP) squamous cell carcinoma of the head and neck (SCCHN) treated at our institution with reirradiation (RRT). Methods Patients received definitive RRT (DRRT) or post-operative RRT following salvage surgery (PRRT) from 2003 to 2011. Measured survival outcomes included loco-regional relapse free survival (LRFS) and overall survival (OS). Results Among 81 patients (PRRT, 42; DRRT, 39), median PRRT and DRRT doses were 60 Gy (12–70 Gy) and 69.6 Gy (48–76.8 Gy). The majority of patients received IMRT-based RRT (n = 77, 95 %). With median follow-up of 78.1 months (95 % CI, 56–96.8 months), 2-year OS was 53 % with PRRT and 48 % with DRRT (p = 0.12); 23 % of patients were alive at last follow-up. LRFS at 2 years was 60 %, and did not differ significantly between PRRT and DRRT groups. A trend toward inferior LRFS was noted among patients receiving chemotherapy with RRT versus RRT alone (p = 0.06). Late serious toxicities were uncommon, including osteoradionecrosis (2 patients) and carotid artery bleeding (1 patient, non-fatal). Conclusions OS of PRRT- and DRRT-treated patients in this series appears superior to the published literature. We used IMRT for the majority of patients, in contrast to several series and trials previously reported, which may account in part for this difference. Future studies should seek to improve outcomes among patients with LRR/NP SCCHN via alternative therapeutic modalities such as proton radiotherapy and by incorporating novel systemic agents.